First report of caprine abortions due to Chlamydia abortus in Argentina - Di Paolo, Leandro Adrián (2019)
Infectious abortions of goats in Argentina are mainly associated with brucellosis and toxoplasmosis. In this paper, we describe an abortion outbreak in goats caused by Chlamydia abortus. Seventy out of 400 goats aborted. Placental smears stained with modified Ziehl-Neelsen stain showed many chlamydia-like bodies within trophoblasts. One stillborn fetus was necropsied and the placenta was examined. No gross lesions were seen in the fetus, but the inter-cotyledonary areas of the placenta were thickened and covered by fibrino-suppurative exudate. The most consistent microscopic finding was found in the placenta and consisted of fibrinoid necrotic vasculitis, with mixed inflammatory infiltration in the tunica media. Immunohistochemistry of the placenta was positive for Chlamydia spp. The results of polymerase chain reaction targeting 23S rRNA gene performed on placenta were positive for Chlamydia spp. An analysis of 417 amplified nucleotide sequences revealed 99% identity to those of C. abortus pm225 (GenBank AJ005617) and pm112 (GenBank AJ005613) isolates. To the best of our knowledge, this is the first report of abortion associated with C. abortus in Argentina.